2017
DOI: 10.1093/imrn/rnx037
|View full text |Cite
|
Sign up to set email alerts
|

The Bernardi Process and Torsor Structures on Spanning Trees

Abstract: Abstract. Let G be a ribbon graph, i.e., a connected finite graph G together with a cyclic ordering of the edges around each vertex. By adapting a construction due to Olivier Bernardi, we associate to any pair (v, e) consisting of a vertex v and an edge e adjacent to v a bijection β (v,e) between spanning trees of G and elements of the set Pic g (G) of degree g divisor classes on G, where g is the genus of G in the sense of Baker-Norine. We give a new proof that the map β (v,e) is bijective by explicitly cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 9 publications
4
53
0
Order By: Relevance
“…In the case of graphs, hypertrees on the vertex set are easily seen to be the duals of the so called break divisors. In this special case, the above bijection-by-dissection agrees with the bijection between spanning trees and break divisors, defined by Bernardi [3] and studied further by Baker and Wang [1]. In [1] the inverse of Bernardi's bijection is described in a way that is formally different from the original Bernardi algorithm.…”
Section: Introductionmentioning
confidence: 53%
“…In the case of graphs, hypertrees on the vertex set are easily seen to be the duals of the so called break divisors. In this special case, the above bijection-by-dissection agrees with the bijection between spanning trees and break divisors, defined by Bernardi [3] and studied further by Baker and Wang [1]. In [1] the inverse of Bernardi's bijection is described in a way that is formally different from the original Bernardi algorithm.…”
Section: Introductionmentioning
confidence: 53%
“…Now we give an alternative proof of Theorem 22, the idea is to prove the commutativity of two finer diagrams separately. In particular, our proof produces a stronger assertion than the proof in [9].…”
Section: The Bernardi Torsors Of Plane Graphs and Plane Dualitymentioning
confidence: 64%
“…In fact, Baker and Wang showed that the torsors induced by Bernardi bijections are isomorphic to the torsors induced by rotor routing if the ribbon structure is planar. Based on these facts as well as some computational evidence, Baker asked whether planar Bernardi bijections come from the above geometric picture [9,Remark 5.2]. In this paper, we answer Baker's question in the affirmative, and we give alternative proofs and sharpenings of Baker and Wang's results.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We would also like to refer the reader to the recent preprint [3], which arrives at another proof of Theorem 3.1 via a completely different route. In that paper, Baker and Wang prove that the bijections obtained by Bernardi in [4,Theorem 45] give rise to another simply transitive action of the sandpile group on the spanning trees of a ribbon graph G with a fixed root vertex.…”
Section: Introductionmentioning
confidence: 99%